2013
DOI: 10.4103/0972-2327.107708
|View full text |Cite
|
Sign up to set email alerts
|

Sleep assessment of children with cerebral palsy: Using validated sleep questionnaire

Abstract: Background:On the basis of clinical experience, it seems that sleep disturbances are common in children with cerebral palsy (CP); however, there is a lack of research and objective data to support this observation.Aim of Work:Our aim was to assess sleep of children with cerebral palsy, using validated sleep questionnaire.Subjects and Methods:one hundred children with diagnosis of CP were investigated via sleep questionnaires, with their ages from 2-12 years. The 100 children with CP were divided into two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
35
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 16 publications
4
35
5
1
Order By: Relevance
“…13 The frequency of bruxism was similar to that reported in previous studies, 3,4,9,14 higher than rates found in Iran 13,15 and lower than rates found in studies involving individuals with cerebral palsy. 5,8,11 The divergence between the rate in the present investigation and those reported in studies involving individuals with cerebral palsy may be due to the small sample sizes in the studies cited. A systematic review of the literature reports that the prevalence rate of bruxism ranges from 5% to 40%, with higher rates found in Brazil in comparison to rates reported throughout the world.…”
contrasting
confidence: 70%
See 2 more Smart Citations
“…13 The frequency of bruxism was similar to that reported in previous studies, 3,4,9,14 higher than rates found in Iran 13,15 and lower than rates found in studies involving individuals with cerebral palsy. 5,8,11 The divergence between the rate in the present investigation and those reported in studies involving individuals with cerebral palsy may be due to the small sample sizes in the studies cited. A systematic review of the literature reports that the prevalence rate of bruxism ranges from 5% to 40%, with higher rates found in Brazil in comparison to rates reported throughout the world.…”
contrasting
confidence: 70%
“…11 Together with dental caries, bruxism has a negative impact on the quality of life of this group of individuals. 8 Knowledge regarding factors associated with bruxism among individuals with developmental disabilities can assist in broadening the understanding of this condition and the establishment of treatment options that are more suitable for this group of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, this finding is important because it emphasizes the need for bruxism monitoring without implying other complex treatments [19,20].…”
Section: Discussionmentioning
confidence: 93%
“…[1] The authors must be lauded for their effort in dealing with sleep assessment with a sleep questionnaire. However, I feel that the study suffers methodologically in picking up and reporting on certain sleep related problems like for example in assessment of nightmares in young children.…”
mentioning
confidence: 99%